Inflation Targeting As a Framework for Monetary Policy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
Inflation distorts prices, erodes savings, discourages investment,stimulates capital flight, inhibits growth, and makes economic planning anightmare. During the past decade, several advanced economies have takena new approach to the age-old problem of controlling inflation throughmonetary policy known as "inflation targeting." This pamphlet explainsthe requirements of putting the new policy in place, the experience of the countries that have tried it, and whether it has applicability todeveloping countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet